Implementation of the Customary Law System in Criminal and Civil Law Enforcement in Coastal Communities - Wadjo, Hadibah Zachra; Uktolseja, Novyta (PAMALI: Pattimura Magister Law Review, 2025)
Introduction: Customary law plays a crucial role in resolving various social conflicts and maintaining justice within the local context.Purposes of the Research: The objective of this article is to examine the role of customary law in resolving criminal and civil disputes within the coastal communities, focusing on the practices of customary law in Negeri Tamilouw, Maluku.Methods of the Research: This research employs a normative-empirical approach, combining literature analysis of customary law with direct observation of its application in the Tamilouw community.Results Main Findings of the Research: The findings of the study show that customary law in the Land of Tamilouw plays an important role in resolving social conflicts through restorative approaches. Communities prefer customary deliberation to taking cases to formal courts, despite challenges in customary law recognition of national law. Customary law is also effective in resolving civil disputes, such as inheritance and property rights, based on local cultural norms.